Does Digital Administration Drive Pedagogical Performance? Assessing the Impact of SIMPATIKA on Classroom Management in Madrasah Education - Erniati, Erniati; Khairi, Azizatul; Sasongko, Rambat Nur (Nurul Jadid University, Probolinggo, East Java, Indonesia, 2026)
This study examines the influence of Digital SIMPATIKA and Contemporary Madrasah Culture on teachers’ classroom management performance, both partially and simultaneously. A quantitative survey approach was applied involving 33 teachers as research participants. Data were collected through validated and reliable questionnaires and analyzed using multiple linear regression, including partial t-tests, a simultaneous F-test, and the coefficient of determination (R²). The results show that Digital SIMPATIKA (X1) has a significant positive effect on classroom management performance (t = 2.652, p = 0.013). In contrast, Contemporary Madrasah Culture (X2) does not demonstrate a statistically significant partial influence (t = 1.587, p = 0.123). However, the regression model as a whole is statistically significant (F = 40.568, p < 0.001). The coefficient of determination (R²) is 0.730 (Adjusted R² = 0.712), indicating that approximately 71.2% of the variance in teachers’ classroom management performance can be explained by the two predictors in the model. These findings suggest that the utilization of Digital SIMPATIKA plays a stronger role in explaining classroom management performance than cultural factors within the context of this study.